Current Perceptions of Lipofilling on the Basis of the New Guideline on "Autologous Fat Grafting" - Prantl, L.; Rennekampff, H. O.; Giunta, R. E.; Harder, Y.; Von Heimburg, D.; Heine, N.; Herold, C.; Kneser, U.; Lampert, F.; Machens, H. G.; Mirastschijski, Ursula; Mueller, D.; et al. (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2016)
Introduction: Autologous fat transfer has recently become an increasingly popular surgical procedure and comprises harvesting, processing and transplantation of adipose tissue, as well as professional follow-up care. This method, as a surgical procedure, can be utilised for trauma-, disease- or age-related soft tissue volume deficits and soft tissue augmentation. As usage is increasing, but the variables of fat harvest, specific indications and fashion of fat transfer are poorly defined, there is a great demand for development of a guideline in the field of reconstructive and aesthetic surgery.Methods:All relevant points were discussed within the scope of a consensus conference including a nominal group process of all societies involved in the procedure and ratified with a strong consensus (>95%). Literature from the standard medical databases over the last 10 years was retrieved, studied and specific guidelines were concluded.Results:Consensus was achieved among all professionals involved on the following points: 1. definition 2. indication/contraindication, 3. preoperative measures 4. donor sites 5. techniques of processing 6. transplantation 7. follow-up care 8. storage 9. efficacy 10. documentation 11. evaluation of patient safety.Conclusion:Definite indications and professional expertise are paramount for autologous fat tissue transfer. Successful transfers are based on the use of correct methods as well as specific instruments and materials. Autologous adipose tissue transplantation is considered to be a safe procedure in reconstructive and aesthetic surgery, due to the low rate of postoperative complications and sequelae.
EVALuna2:32822